The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1094/pdis-11-10-0796
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Prevalence of Species of Binucleate Rhizoctonia Fungi in Growing Medium, Leaf Litter, and Stems of Container-Grown Azalea

Abstract: Rhizoctonia web blight is an annual problem on container-grown azalea (Rhododendron spp.) in the southern and eastern United States but little is documented about the distribution or persistence of Rhizoctonia spp. in container-grown azalea. Sixty web-blight-damaged azalea plants (‘Gumpo White’) were collected in August 2005 and 2006 and arranged in a completely randomized design on an outdoor irrigation pad. A nylon mesh bag containing 30 necrotic leaves collected from web-blight-damaged ‘Gumpo White’ azalea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…; Copes et al. ). The diagnostic symptom pattern is a leaf blight that develops without intermediate stages.…”
Section: Introductionmentioning
confidence: 99%
“…; Copes et al. ). The diagnostic symptom pattern is a leaf blight that develops without intermediate stages.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal studies on Rhizoctonia web blight on azalea in south ern M ississippi have reported several different weather conditions that are conducive for disease development (4)(5)(6)(7)(8). Rhizoctonia web blight development on azalea was initially correlated with air tem peratures between 25 and 30°C for 6 to 8 h per day, relative humid ity >95% for >8 h per day, and/or leaf wetness for >6 h per day (7).…”
mentioning
confidence: 99%
“…The rate and degree o f web blight development differed between wet, moderate, and dry years, and weather variables o f tem pera ture, rainfall, and duration o f leaf wetness do influence disease development and control (4)(5)(6)(7)(8). Rhizoctonia web blight on azalea behaves like a polycyclic disease (7,8,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations